Public infrastructure performance in developing countries : the case of electric power and telecommunications industries in Pakistan - Ghafoor, Abdul (Aldershot, Eng. ; Brookfield, VT : Ashgate, 2000)
This book contains a comprehensive review of literature and explain the basic concepts of state-owned enterprises related to electric power and telecommunication sectors, it could provide an overview to the beginners in this field.
Includes bibliographical references (p. 203-217).
osa 28/09/2016
Loan
Keywords: Public utilities; Telecommunication; Electric utilities $1 (BPakistan.s; Pakistan..